Not enough traction: Barriers that aspiring researchers from low- and middle-income countries face in global health research - Constance S. Shumba; Adelaide M Lusambili (International Society of Global Health, 2021)
There is a growing concern of low representation of researchers from low-middle-income countries (LMICs) in the publication of global health research in high-impact peer-reviewed journals. Nobody denies that researchers from the developing world generally face several obstacles to publishing their research. In this viewpoint, we share some of the barriers we have observed from our experience working in both academia and global health practice in low and middle-income countries such as limited opportunities for research funding, gender disparities, and language barriers. Beyond presenting the barriers, we also provide some pragmatic solutions to addressing these barriers through increased research financing, capacity building, gender equity and inclusion, and editorial support. Most importantly, we call for setting a new level of ambition in redressing the imbalances and actualizing the leadership and emergence of a veritable critical mass of LMICs researchers.